Enhancing Learning Through Game Flow: A Case Study for Epistemic Game “Working With Water” (London Journal of Research In Computer Science and Technology, 2025)
Epistemic video games, interpreted as video games pursuing new knowledge through the mechanism that concatenates  practices and cognition, grab numerous attention on account of their extensive implementation since COVID-19. The  corresponding academic explorations into the players, especially indicating the students, have largely integrated in game  enjoyment and the principals exerted. Understanding the essential factors that promote game enjoyment that aligns with  educational purposes is crucially important for clarifying the mechanism of epistemic games. Consequently, the present  study adopts the GameFlow model presented by Sweetser and Wyeth (2005), whose accuracy has been verified and yields to evaluate enjoyment of video games by examining specific criteria under eight elements: concentration, challenge, player  skills, control, clear goals, feedback, immersion, and social interaction of the model. The highly acclaimed epistemic game  “Working with Water” is elected to conduct a case study by implementing the Game Flow model. The result indicates that  the overall values for Game Flow cohere with the performance, usability, and potentiality of the epistemic games. The  model performs well in the evaluation of epistemic games to a large extent. but simultaneously limited to the intrinsic harshness of the specific genre that differs from others in the degree of enjoyment. As a result, the evaluating model based  on GameFlow is worthy of inquiry in an educational context for further investigation.
Keywords: learning; case study; Epistemic games; GameFlow; Game evaluation